CONSTRUCTION AND PERFORMANCE STUDY OF A ROCK BED BLACK AGATE HOME TYPE SOLAR AIR HEATER WITH SOLAR DRYER - Nurmanova, Makhfuza Urozovna (Educational Research in Universal Sciences, 2022)
This article presents an evaluation of the construction and performance of a Black Agate stone bed. The house has a new type of solar air heating system with a total area of 1m2. The system is made from locally available materials and installations, operations are carried out in the developing country of Uzbekistan. Rock is used as thermal mass storing heat from the sun and releasing heat in the absence of effective radiation. Drying indicators were with hygroscopic products is carried out using a solar dryer. Solar air heater performance is rated differently air flow rate and the optimal air flow rate is 0.0122 kg/s. The result shows that the solar air heater is capable of this maximum outlet air temperature is 66oC, relative humidity is 1%, thermal efficiency is 39% and delivered energy is 4.4 kW. The system is also able to deliver efficient hot air during non-sunlight hours duration 6 hours. The maximum moisture removal efficiency of the dryer is 36%. The total moisture removal for 9 hours of drying is 25% without affecting the quality and identity of the product moisture absorption is 7 gm/kW.